Exploration of adaptation among first-year students at Teacher Education Institutes (IPG) - Tengku Norhani Tengku Besar; Nor Shafrin Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2021)
The first-year in institutes of higher education is a challenging phase for new students. They need to adapt to the academic and social environment that is different from school culture. This transition process requires them to have a high level of resilience to face the challenges of the campus world. This study aims to explore the adaptation problems among the students of the Bachelor of Education Preparatory Program (PPISMP) at Teacher Education Institutes (IPG). The respondents of this study consisted of four lecturers, four counselors and 30 PPISMP students. Semi structured interviews were conducted to lecturers and counselors while students underwent a Nominal Group Technique (NGT) session. The interviews and discussions of NGT were then transcribed and analyzed using content analysis to form appropriate categories or themes. The findings show that most participants have shown that the problem of adaptation is often faced by PPISMP students. The adaptation problems are related to academic, social, personal, emotional and institutional attachment. The findings of this study are expected to contribute towards the formation and development of appropriate intervention methods to assist the well-being of PPISMP students in IPG in adapting to new environments and increasing their resilience.